(untitled) (Revista Contexto & Educação, 2026)
This article stands out for its qualitative and exploratory nature, as it investigates what has been produced about initial training in the Pedagogy Course, with regard to teacher training, for teaching committed to children in the specificity of Early Childhood Education. It was decided to carry out a Systematic Literature Review (with detailed steps in the article) using the Scientific Electronic Library Online, the Capes Periodicals Portal and the Brazilian Digital Library of Theses and Dissertations as search sources. This review contributed to the Master’s Dissertation presented to the Postgraduate Program in Education (PPGE) at the Federal University of Santa Maria (UFSM). As main findings, it is worth highlighting that the selected and analyzed research reports on the fact that the history of Early Childhood Education and teaching at this stage are still very recent in Brazil, in addition to presenting a certain timeline of the historical paths of the Pedagogy Course in Brazil. The need to direct studies that contemplate Pedagogy courses and the specificity of teaching in Early Childhood Education is also identified by different research, being presented as a gap and as a need for new dialogues. Another finding is in line with the assumptions that, although the Pedagogy course trains Pedagogues to work in different areas, training for the first stage of basic education still occupies a small space in the course curricula and tends to be even smaller with regard to the specificities of teaching in Early Childhood Education.